Population of The Javan Surili Langur Presbytis comata in The Taman Safari Indonesia Bogor Forest Area - Sinaga, Walberto; Manansang, Jansen (Media Konservasi, 2024)
Taman Safari Indonesia Bogor is a buffer zone for the Taman Nasional Gunung Gede Pangrango conservation forest area and is one of the habitats for the Javan surili langurs, but there is no research data on wild Javan surili langur populations. The object of research is to find out how many populations of Javan surili langurs are in the TSI Bogor forest area. The research method used the line transect method by collecting data on the number of individuals, the number of groups, the sex ratio, and the age structure. The research was conducted in four observation areas with varying lengths, observations were made at (06.00 - 17.00 WIB), and four repetitions were carried out on each observation path, the results showed that there were 16 Javan surili langurs individuals divided into one group, and the estimated population density was 0.06 individual/ha. The sex diversity of male and female surili langurs in the TSI Bogor forest area is 1:6 where the female Javan surili langurs are more than the male Javan surili langurs and for the age structure the largest Javan surili langurs are in the adult age class with a percentage of 43.75%, juvenile 31.25%, and the percentage of infant is 25%.